2017
DOI: 10.1080/09540121.2017.1384532
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and risk of falls and fractures for patients with HIV infection and substance dependence

Abstract: Although people with HIV infection (PLWH) are at higher risk of polypharmacy and substance use, there is limited knowledge about potential harms associated with polypharmacy such as falls and fractures in this population. The study objective was to determine whether polypharmacy, as measured by the number and type of medication, is associated with falls and fractures among PLWH and DSM-IV substance dependence in the past year or ever injection drug use (IDU). We identified the number of medications by electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…This association is established among older adults 26,27 and has been suggested by other investigators among PLWH. 4,12 The stronger association between benzodiazepines, muscle relaxants and serious falls among PLWH relative to uninfected comparators is particularly striking. These medications may interact with ART or direct effects of the virus may increase their impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association is established among older adults 26,27 and has been suggested by other investigators among PLWH. 4,12 The stronger association between benzodiazepines, muscle relaxants and serious falls among PLWH relative to uninfected comparators is particularly striking. These medications may interact with ART or direct effects of the virus may increase their impact.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study that included uninfected individuals found that hepatitis C virus infection (HCV), female sex, obesity, smoking and clinical imbalance symptoms were associated with falls, but that age, HIV serostatus, and other comorbidities were not. 5 Others suggest that comorbidity count 7 and the number of medications prescribed 11,12 are associated with fall risk among PLWH, but neither of these studies provided comparisons with uninfected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Fall research in the HIV+ population identified multimorbidity, polypharmacy, and functional impairment as important fall risk factors [ 1 ]. In addition to the total number of medications prescribed (polypharmacy), specific medications were associated with falls, particularly those that were active in the central nervous system (CNS) such as opioids, muscle relaxants, and benzodiazepines [ 7 , 8 ]. Frailty and peripheral neuropathy have also been associated with falls in this population as have symptoms of dizziness or imbalance [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high rate noted in our young cohort may be explained by a different HIV profile to that of PWH in HIC studies. Although most HIC studies found no association between falls and viral load, these studies included cohorts with mostly undetectable viral loads [1, 5, 8, 12, 30]. The discordance noted between ART use and virologic suppression in our sample may be reflective of South African PWH [37], where poor ART adherence or virological failure may be common [16].…”
Section: Discussionmentioning
confidence: 89%